2021
DOI: 10.3389/fpsyg.2021.629467
|View full text |Cite
|
Sign up to set email alerts
|

Prosocial Orientation of Russians During the COVID-19 Pandemic: Caring for Others and Yourself

Abstract: To mitigate the potentially devastating effects of the COVID-19 pandemic, it is vital to identify psychosocial and moral resources. The care, preservation, protection, and well-being of social communities are attributes of prosocial behavior that can be such a resource. The purpose of the study is to identify the features of prosocial orientation of Russian youth during the COVID-19 pandemic, as well as to identify strategies for prosocial behavior during the COVID-19 pandemic. The sample consisted of 447 peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
1
5
0
1
Order By: Relevance
“…These findings are consistent with previous research suggesting that the structure of volunteering motives is not monolithic (Mousa, Freeland-Graves 2017;Kulik 2021). Before and during the COVID-19 pandemic, two behavioral options, i. e., 'giving' and 'exchanging' help, were possible for Russian volunteers, which is consistent with the research by Kislyakov and Shmeleva (2021). This study revealed that 'pandemic' volunteering could be of an ad hoc nature, becoming integrated into people's everyday lives.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are consistent with previous research suggesting that the structure of volunteering motives is not monolithic (Mousa, Freeland-Graves 2017;Kulik 2021). Before and during the COVID-19 pandemic, two behavioral options, i. e., 'giving' and 'exchanging' help, were possible for Russian volunteers, which is consistent with the research by Kislyakov and Shmeleva (2021). This study revealed that 'pandemic' volunteering could be of an ad hoc nature, becoming integrated into people's everyday lives.…”
Section: Discussionsupporting
confidence: 91%
“…In this case, it is a manifestation of a proactive behavioral strategy of 'caring for others' (true altruism, expressed in forms of volunteering, helping a stranger, and charity despite the risk of contracting a coronavirus infection) as the prosocial orientation of Russians during the COVID-19 pandemic (Kislyakov, Shmeleva 2021).…”
Section: Volunteering In the Times Of The Pandemic: Stability Of Motivesmentioning
confidence: 99%
“…'Responsible citizenship' seemed to be an important aspect of their identity for some people during the pandemic (Kislyakov and Shmeleva 2021;Kholyavin 2020;Tartakovskaya 2021). In our sample, non-routine workers explained that they voluntarily followed public guidelines and were careful not to put others at risk (thus adhering to the WHO ethics: 'no one is safe until everyone is safe').…”
Section: Resultsmentioning
confidence: 99%
“…Germany also emphasised its strength through humanitarian actions 57 , such as donations and ensuring transparency and access to vaccines, even in countries that are not as strong and do not have sufficient financial resources. Kislyakov and Shmeleva (2021) showed that Russia's prosocial orientation during the Covid-19 pandemic, highlighting an understanding of diversity and caring for others and oneself, as one of the intercultural competencies. However, the decision regarding the obligation to vaccinate solely with the Russian vaccine Sputnik, enforced a strict and professional attitude of Russia and the confidence in its resources (such as the Sputnik vaccine).…”
Section: Findings and Discussionmentioning
confidence: 99%